2013
DOI: 10.1111/eos.12085
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor gene polymorphisms with chronic and aggressive periodontitis in Jordanian patients

Abstract: Vitamin D acts through binding with vitamin D receptor (VDR) and is responsible for regulating bone metabolism and mineralization; it also suppresses the immune system. The aim of this study was to investigate if VDR gene polymorphisms are associated with chronic periodontitis (CP) and aggressive periodontitis (AgP) in a Jordanian population. A total of 99 patients with CP, 63 patients with AgP, and 126 controls were genotyped using PCR-restriction fragment length polymorphism (RFLP) for BsmI, ApaI, and TaqI s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…The allelic frequency of ‘T’ vs ‘t’ and ‘A’ vs ‘a’ were 65 vs 35% and 66 vs 34% respectively in Syrian population. Comparison of frequency distribution of different genotypes and alleles of VDR gene was done between Syrian and different populations that mentioned in North Indian study ( Bid et al, 2005 ), Turkey ( Gunes et al, 2008 ), Iran ( Nosratabadi et al, 2010 ) and Jordan ( Karasneh et al, 2013 ) using χ 2 tests. In this study, no differences in the distribution of genotypes and alleles of Taq-I were found between Syrian individuals and each of the populations of Jordan, Sweden, Black Pennsylvania and Australia as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The allelic frequency of ‘T’ vs ‘t’ and ‘A’ vs ‘a’ were 65 vs 35% and 66 vs 34% respectively in Syrian population. Comparison of frequency distribution of different genotypes and alleles of VDR gene was done between Syrian and different populations that mentioned in North Indian study ( Bid et al, 2005 ), Turkey ( Gunes et al, 2008 ), Iran ( Nosratabadi et al, 2010 ) and Jordan ( Karasneh et al, 2013 ) using χ 2 tests. In this study, no differences in the distribution of genotypes and alleles of Taq-I were found between Syrian individuals and each of the populations of Jordan, Sweden, Black Pennsylvania and Australia as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In this table, the data were adapted basically from the North Indian study ( Bid et al, 2005 ) and studies from Jordan (+) ( Karasneh et al, 2013 ), Turkey (+) ( Gunes et al, 2008 ) and Iran (+) ( Nosratabadi et al, 2010 ). Whereas the distribution of genotypes and alleles of Apa-I was similar in Syrians compared to populations of Jordan, North India, Turkey, France, Greece and Black Pennsylvania as shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inagaki et al (2003) and Naito et al (2007) reported that the AA genotype was associated with a higher risk of severe CP and with more advanced alveolar bone loss. However, Karasneh et al (2013) observed that CP occurred more frequently in subjects with AA genotype. In addition, studies of the impact of Bsml and Fokl polymorphisms on the development of periodontal inflammation have provided ambiguous results.…”
Section: Periodontitismentioning
confidence: 89%